ETHNIC TOLERANCE IN ISLAM: NOTES FOR A DISCUSSION OF RELIGIOUS IDEALS AND HISTORICAL FACTS - Marín Guzmán, Roberto (2013)
This paper reviews the historical and literary sources of Islam seeking to show how ethnic tolerance has played an important role in these writings , at different times in Middle East history, being broken on many occasions.Rivalries between peoples of Middle East are put forth, particularly the hierarchical position that had kept the Arabs over Persians, Berbers and other peoples who had converted to this religion. Therefore, the article present the ways in which ethnic acceptance and tolerance historically haven’t been taken into practice.